Improving Web-Based Learning by Using Improved and Well Designed Course Management Systems - Hannafin, Robert; Ioannou, Andri (My University, 2006)
Web-Based Learning (WBL) has increased dramatically in the past 10 years. Issues facing WBL include learner needs, instructional process, issues of access, and the changing roles of teachers and students. Instructors’ ability to address these issues is largely dependent on the software technology used to develop and deliver the online courses. Course management systems (CMSs), like WebCT and Blackboard, are the mediums of choice for developing and delivering online courses in recent years, serving thousands of K20 schools worldwide. Good course design is essential in WBL, but limited by the technologies used. Distant teaching and learning can be as effective as the traditional face-to-face when assisted by well-designed technologies. The purpose of this paper is to explain how to improve distance education by improving CMSs. We need to take a critical look at tools like WebCT and Blackboard and recommend improvements that may improve student learning experiences.
Keywords: Web-Based Learning; WebCT